Efficiency of Three-Stone Fire and Improved Cooking Stoves using on-farm and off-farm fuels in semi-arid Tanzania - Hafner, Johannes M.; Uckert, Götz; Hoffmann, H.K.; Rosenstock, Todd S.; Sieber, S.; Kimaro, Anthony A. (Elsevier, 2020)
In Tanzania, fuelwood availability for cooking is an increasing challenge for rural households struggling to meet this need. Here, a possible pathway for smallholder farmers to reduce their dependency on off-farm fuelwood is evaluated. We compare the cooking performance of on-farm produced fuels, like wood from Gliricidia sepium (Jacq.) Kunth ex Walp. and Cajanus cajan (L.) Millsp. (pigeon pea stalks) with the off-farm fuelwood species Mimusops obtusifolia (Lam. Sapotaceae). Fuel performance was tested using Three-Stone Fire stoves and artisan-made Improved Cooking Stoves. We conducted 75 cooking tasks, cooking a standardized pre-defined meal with two pots in five villages in Chamwino and Kongwa districts, Dodoma region. The Controlled Cooking Test design assessed four key performance indicators: (1) time until water is boiling in pot A, (2) time until food item in pot A is ready to be consumed, (3) total cooking time per meal, including food items in pots A and B, (4) total fuel consumption per meal, including food items in pots A and B. Compared to the off-farm fuel, on-farm fuels perform better across the four key performance indicators. The results show that with regard to total cooking time per meal, including food items in pots A and B and total fuel consumption per meal, including food items in pots A and B, Improved Cooking Stoves used less time and fuel than Three-Stone Fire stoves. Regarding the key performance indicators time until water is boiling in pot A and time until food item in pot A is ready to be consumed, Three-Stone Fire stoves are faster than Improved Cooking Stoves, thus suggesting that Three-Stone Fire stoves are beneficial when cooking with only one pot. In order to reduce fuel and time consumption during cooking, the results suggest switching from off-farm to on-farm fuels; however, the choice of stove will depend on the cooking task performed.